THE FEATURES OF THE INNOVATIONS OF ARCHITECTURAL ENVIRONMENT IN THE RESORT-CITY - Arpine Sarkisovna Torosyan (Современная наука и инновации)
The article considers the actual problem of interaction between nature and the urban environment. The need of rethinking the natural potential, the role of green areas in the resort city with the help of innovation in construction and architecture was viewed. The examples of the foreign experience in the development of "biotechnology" not only at the landscape level, but in the urban system are given.